Evaluation of anesthesia management in laparoscopic radical prostatectomy surgeries: A retrospective clinical study (Annals of Medical Research, 2021)
None
Keywords: Anesthesia Management; Laparoscopic Radical Prostatectomy; Retrospective analysis.